Description of the first species of Scambus Hartig (Hymenoptera, Ichneumonidae) from Peru, with a key to the Neotropical species - Gómez, Isrrael C.; Yabar-Landa, Erick (Zootaxa, 2015)
In this work we describe and illustrate two new species of Scambus from the Peruvian Andes and the Andean-Amazonian interface: S. amazonicus Gómez sp. n., and S. incanus Gómez sp. n. These are the first Scambus species described from Peru. In addition, we provide an identification key to the Neotropical species of the genus.